Application of Taguchi Method in the Optimization of Swimming Capability for Robotic Fish. (25th May 2016) - Li, Liang; Lv, Jiang; Chen, Wang; Wang, Wei; Zhang, Xing; Xie, Guangming
In this paper, we applied the Taguchi method to evaluate the maximum swimming speed of a robotic fish under the limitation of the output of the motor. Four factors were considered in the optimization: the caudal-fin aspect ratio, the caudal fin stiffness, the oscillating frequency and the stiffness of the spring that transmits forces from the actuators to the foil. Because of the power limitations, the parameter's space was irregular. Since the Taguchi method requires a regular parameter space, we divided the parameter space into a regular space and the remaining irregular spaces. Within only 25 trials, the frequency and the spring stiffness were determined as the main factors in the regular space by the orthogonal design. Six more trials were carried out in the remaining irregular space with a higher frequency and spring stiffness. The fastest swimming speed of 870 mm/s, approximately 2.6 BL ( Body Lengths )/ s, was acquired, when the frequency reached 12 Hz and with infinite spring stiffness. This method is efficient for exploring the maximum locomotor capabilities of robotic fish and may also be useful for other robots as no modelling is required.